Tolerance as an essential characteristic of a secondary linguistic persona (with exemplary exercises for English lessons) - D. K. Voronina; S. E. Tsvetkova (Вестник Северо-Кавказского федерального университета)
Introduction. Language acquisition and speech skills development are not the only conditions for successful intercultural communication. Productive speech interaction is largely determined by the ability to accept and understand differences, tolerate the otherness.Goal. The study aims to consider the concept of tolerance as a basic personal characteristic being formed in language classes, to describe a system of exercises that form tolerance in English lessons in high school.Materials and methods. The article presents a theoretical analysis of the linguistic and cultural foundations of foreign language school teaching and works on the intercultural approach in language education. The concept of “tolerance” in studies of the psychological component of intercultural communication is considered. The process of learning English in high school is modeled.Results and discussion. Based on the studied interpretations, the main components of a complex multi-component personality characteristic are identified. The system of exercises promoting the stages of the intended characteristic formation is described and illustrated by examples. Through step-by-step, systematic learning activities in an English lesson, high school students will develop relevant personality characteristics.Conclusion. The main findings of the study include: 1) the description of the Foreign Language course potential for the tolerance formation among high school students; 2) analysis of researchers’ interpretations regarding the clarification of the essence and components of the tolerance concept; 3) justification of the stages of foreign language educational activities for the purpose of forming tolerance; 4) a system of exercises with specific educational tasks for English lessons in high school. The results of the study can be extrapolated to other foreign language learning conditions.